Evaluation of a novel skin care product for the management of chemotherapy–related dermatologic toxicities: A quasi-experimental study. (April 2023) - Robijns, Jolien; Lodewijckx, Joy; Claes, Marithé; Tuts, Laura; Lenaerts, Melissa; Wessels, Tim; Requilé, Annelies; Luyten, Daisy; Verheezen, Jolanda; Joosens, Eric; Mebis, Jeroen
Abstract: Purpose: Evaluate the efficacy of a novel skincare product for the management of chemotherapy-related dermatological toxicities. Methods: A monocentric, prospective, interventional, open-label, pretest-posttest, single-group study with cancer patients receiving chemotherapy (n = 100) was set up. All enrolled patients applied the emollient daily to their face and body for three weeks. The severity of the skin reactions was evaluated by a researcher using the Common Terminology Criteria for Adverse Events (CTCAE) v5.0 at baseline and end of the trial. Patient-reported outcomes (PROs) included the frequency and severity of skin symptoms (Numerical rating scale, NRS), quality of life (QoL; Skindex-16 and Dermatology Life Quality Index), Patient Benefit Index (PBI), and treatment satisfaction. PROs were collected at baseline, weekly, and at the end of the trial. Results: According to the CTCAE and NRS, the novel emollient significantly improved the severity and frequency of xerosis and pruritus (Ps ≤ .001). A significant reduction in the NRS score for frequency of erythema was measured (p < .001). The frequency and severity of burning and pain did not change. Regarding the patients' QoL, no beneficial effect of the skin care product was measurable. 44% of the patients experienced at least one patient-relevant treatment benefit. 87% of the patients were satisfied with the emollient and would recommend it. Conclusions: This study shows that the novel emollient significantly reduced chemotherapy-induced skin toxicity, more specifically xerosis and pruritus without hampering patient's QoL. Future research is needed to make definite conclusions using a study design including a control group and a long-term follow-up. Highlights: Xerosis and pruritus are the most common skin toxicities induced by chemotherapy. A novel hydrating emollient showed beneficial effects on xerosis and pruritus. The dermatologic adverse events did not hamper patients' quality of life. 87% of the patients were satisfied with the novel emollient.